2002
DOI: 10.1210/rp.57.1.295
|View full text |Cite
|
Sign up to set email alerts
|

Definition of the Molecular and Cellular Mechanisms Underlying the Tissue-selective Agonist/Antagonist Activities of Selective Estrogen Receptor Modulators

Abstract: The term selective estrogen receptor modulators describes a group of pharmaceuticals that function as estrogen receptor (ER) agonists in some tissues but that oppose estrogen action in others. Although the name for this class of drugs has been adopted only recently, the concept is not new, as compounds exhibiting tissue-selective ER agonist/antagonist properties have been around for nearly 40 years. What is new is the idea that it may be possible to capitalize on the paradoxical activities of these drugs and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 74 publications
2
61
1
1
Order By: Relevance
“…[94]. Whether ERs act as homodimers versus heterodimers for these effects requires further investigation.…”
Section: The Role Of Erα (And Erβ) For Functional Effects Of Estogensmentioning
confidence: 99%
“…[94]. Whether ERs act as homodimers versus heterodimers for these effects requires further investigation.…”
Section: The Role Of Erα (And Erβ) For Functional Effects Of Estogensmentioning
confidence: 99%
“…Estrogens and ERs are vital for ovarian development and function (Knapczyk et al 2008, Wąsowicz et al 2011. By forming a complex with the receptor, ZEN initiates conformational changes that cause estrogen-responsive elements (EREs) to bind to DNA, which induces/inhibits the transcription of estrogen-sensitive genes (Mayr et al 1992, McDonnell et al 2002. This balance is determined mostly by the type of ERs in the involved tissue, and the relative levels of ligands and receptors (McDonnell et al 2002, Shang and Brown 2002, Singh et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies conducted with synthetic antiestrogens, such as tamoxifen, have shown that the agonist/antagonist profile of a ligand varies with the tissue and the target gene considered. This led to the term of selective estrogen receptor modulators (SERMs) to define this class of drug [13][14][15]. ER activity can also be modulated through indirect activation of the ER by growth factors or cytokines independently of the binding of natural or synthetic hormones [16,17].…”
Section: Introductionmentioning
confidence: 99%